Auditor Reputation, Audit Tenure, and Earnings Surprise Benchmark on Audit Quality: Evidence from Basic Materials Sector Companies in Indonesia - Ramadhani, Anindya; Abbas, Dirvi Surya (Media Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of Auditor Reputation, Audit Tenure, and Earnings Surprise Benchmark on Audit Quality in Indonesian Basic Material companies during the 2021–2024 period, while considering Auditor Specialization as a situational context. The data were obtained from audited annual financial statements and annual reports of companies listed on the Indonesia Stock Exchange. The sample consists of 73 companies, yielding 292 firm-year observations, selected using purposive sampling based on established criteria. Data were analyzed using panel logistic regression with the assistance of E-Views 12. The results indicate that Auditor Reputation and Audit Tenure significantly enhance Audit Quality, while Earnings Surprise Benchmark reflects auditors’ heightened scrutiny under abnormal earnings conditions. Furthermore, the split-sample analysis reveals that these relationships are stronger when auditors possess high industry specialization, highlighting its role as a situational factor. These findings underscore the importance of auditor competence and industry-specific expertise in ensuring high-quality audits. This study provides practical insights for audit firms and regulators in designing strategies to improve audit quality in high-risk and volatile sectors.